Editorial: On Editorials! - McCullough, Karen (ARCTIC, 1989)
Given today's exciting and rapidly evolving developments in the Canadian North, the practice of masthead editorials was initiated to provide some degree of topicality to the multidisciplinary journal Arctic. This practice has resulted, much to our delight, in a substantial increase in letters to the editor - some commending and others strongly disagreeing with the trenchant and thought-provoking ideas put forth in the editorials. An editorial is an opinion piece or proposal written by an individual or group of individuals who wish to express a particular viewpoint on an issue of current relevance. The masthead editorial in Arctic is specifically designed to promote feedback from the readership and encourage our members to actively participate in the scholarly debate of important events and issues affecting the North now and in the future. A more active participation by the members through guest editorials and letters to the editors can only serve to enhance the value of and interest in the journal. .